Les transferts de technologie nord-sud en matière de télécommunications par satellites - Prémont, Marie-Claude (Les Cahiers de droit, 1986)
While the industrialized countries are already involved in the new information age, the developing countries are still trying to achieve some measure of industrialization. Although by themselves the satellite telecommunication systems will not solve all the problems of developing countries, nevertheless, they could facilitate the shortcircuiting of a number of preliminary steps leading to the new communications era. However, as most of the knowledge concerning these satellite systems — from their design until the final stage of production — are concentrated in industrialized nations, this leaves developing countries in a vulnerable and dependent position. This article analyses some of the established and evolving legal norms towards the promotion of technological parity between the industrialized and non-industrialized nations ; these can be grouped under five specific headings : 1. « Space Law »; 2. « New International Economic Order »; 3. « Right to Communicate » ; 4. « Code of Conduct on Technological Transfer » ; 5. « New International Law of Survival ». Following these legal considerations, we analyse the types and means of technological transfers taking place between industrialized and non-industrialized countries. In this connection, it is important to distinguish between the transfer of specified equipment only from that of its engineering. We examine these transfers, first following the initiative of the government-sponsored agencies, and second, as a transaction taking place on the free international market. In our study, it is evident that while non-industrialized countries have access to satellite communications equipment, this however does not apply to their engineering. Will the new rules of international law be capable to launch a free flow of technological knowledge between the industrialized and non-industrialized countries ? On this point, we express our reservations.